Pulmonary Hypertension Complicating Interstitial Lung Disease and COPD - Shino, Michael Y.; Lynch, Joseph P., III; Saggar, Rajeev; Abtin, Fereidoun; Belperio, John A.; Saggar, Rajan (Seminars in Respiratory and Critical Care Medicine, 2013)
Pulmonary hypertension (PH) may complicate parenchymal lung disease, specifically interstitial lung diseases and chronic obstructive pulmonary disease, and uniformly increases the mortality risk. The epidemiology and degree of PH is variable and unique to the underlying lung disease. The clinician should exercise a high index of suspicion for PH complicating parenchymal lung disease especially given the nonspecific symptomatology and the limitations of echocardiography in this patient population. In general, PH-specific therapies in this setting have been poorly studied, with concern for increased shunting and/or ventilation/perfusion (V/Q) mismatch and resultant hypoxemia. A better understanding of the mechanisms underlying PH related to parenchymal lung disease may lead to novel pharmacological targets to prevent or treat this serious complication.
Keywords: interstitial lung disease; pulmonary hypertension; idiopathic pulmonary fibrosis; sarcoidosis; chronic obstructive pulmonary disease